Limited Memory BFGS Method for Nonlinear Monotone Equations (Journal of Computational Mathematics, 2018)
In this paper, we propose an algorithm for solving nonlinear monotone equations by combining the limited memory BFGS method (L-BFGS) with a projection method. We show that the method is globally convergent if the equation involves a Lipschitz continuous monotone function. We also present some preliminary numerical results.
Keywords: Limited memory BFGS method; Monotone function; Projection method.